Short-term high-fat diet alters substrate utilization during exercise but not glucose tolerance in highly trained athletes - Staudacher, H. M.; Carey, A. L.; Cummings, N. K.; Hawley, J. A.; Burke, L. M. (International Journal of Sport Nutrition and Exercise Metabolism, 2001)
We determined the effect of a high-fat diet and carbohydrate (CHO) restoration on substrate oxidation and glucose tolerance in 7 competitive ultra-endurance athletes (peak oxygen uptake [VáO2peak] 68 ± 1 ml á kg-1 á min-1; mean ± SEM). For 6 days, subjects consumed a random order of a high-fat (69% fat; FAT-adapt) or a high-CHO (70% CHO; HCHO) diet, each followed by 1 day of a high-CHO diet. Treatments were separated by an 18-day wash out. Substrate oxidation was determined during submaximal cycling (20 min at 65% VáO2peak) prior to and following the 6 day dietary interventions. Fat oxidation at baseline was not different between treatments (17.4 ± 2.1 vs. 16.1 ± 1.3 g á 20 minÐ1 for FAT-adapt and HCHO, respectively) but increased 34% after 6 days of FAT-adapt (to 23.3 ± 0.9 g á 20 min-1, p < .05) and decreased 30% after HCHO (to 11.3 ± 1.4 g á 20 min-1, p < .05). Glucose tolerance, determined by the area under the plasma [glucose] versus time curve during an oral glucose tolerance (OGTT) test, was similar at baseline (545 ± 21 vs. 520 ± 28 mmol á L-1 á 90 min-1), after 5-d of dietary intervention (563 ± 26 vs. 520 ±18 mmol á L-1 á 90 min-1) and after 1 d of high-CHO (491 ± 28 vs. 489 ± 22 mmol á LÐ1 á 90min-1 for FAT- adapt and HCHO, respectively). An index of whole-body insulin sensitivity ( SI, 10000/ Öfasting [glucose] 3 fasting [insulin] 3 mean [glucose] during OGTT 3 mean [insulin] during OGTT) was similar at baseline (15 ± 2 vs. 17 ± 5 arbitrary units), after 5-d of dietary intervention (15 ± 2 vs. 15 ± 2) and after 24 h of CHO loading (17 ± 3 vs. 18 ± 2 for FAT- adapt and HCHO, respectively). We conclude that despite marked changes in the pattern of substrate oxidation during submaximal exercise, short-term adaptation to a high-fat diet does not alter whole-body glucose tolerance or an index of insulin sensitivity in highly-trained individuals.